Vulvar lichen sclerousus: case report - Salazar-Marcatoma, Liliana (2025)
INTRODUCTION: Vulvar lichen sclerosus is a chronic inflammatory skin disease with a clear predilection for the anogenital region that is commonly underdiagnosed; It is the most common vulvar dermatosis associated with pruritus. OBJECTIVE: To report a clinical case of a patient with vulvar lichen sclerosus. CLINICAL CASE: 51-year-old quechua-speaking patient treated for vulvar itching of two years' duration. On clinical examination, a wrinkled hypopigmented plaque was found covering the vulva, the perineal body, the perianal area and the labia minora were adhered, defining a 5mm excoriative lesion in the vulvar fork. The diagnosis was clinical and confirmed with histopathology. Local corticosteroids were administered and the patient progressed with substantial improvement. CONCLUSION: The diagnosis of vulvar lichen sclerosus is usually clinical when the clinical features are typical; histological examination is not always essential. In the early stages of the disease, diagnosis can be difficult and a clinical scoring system is applied that includes typical signs, with a score >4 being diagnostic of LSV with 90% certainty.